Fancying the New Rich and Famous? Explicating the Roles of Influencer Content, Credibility, and Parental Mediation in Adolescents’ Parasocial Relationship, Materialism, and Purchase Intentions - Lou, Chen; Kim, Hye Kyung (Frontiers in Psychology, 2019)
While social media influencers are gleaning increasing trust and investment from brands, advertisers, and followers, insights on the role of influencers in adolescents’ relationship formation and consumption behaviors are still rare. Drawing on the literatures of influencer content value, influencer credibility, parental mediation, and parasocial relationship, this study proposed a conceptual model that expounds the appeal of influencers among adolescents. To test the model, we administered an online survey – recruited in proportion to demographic quotas (i.e., age, gender and ethnicity) – among 500 U.S. adolescents (aged 10- to 19-years old) via Qualtrics panel. Results revealed that, the entertainment value of influencer-generated content, influencer expertise, trustworthiness, attractiveness, and followers’ perceived similarity to their favorite influencers, are positively related to the perceived parasocial relationship between adolescent followers and their favorite influencers, which in turn, are associated with adolescents’ materialistic views and purchase intentions. We also explored the role of parental mediation of adolescents’ social media use in their parasocial relationship with influencers. Results indicate that, neither active mediation nor restrictive mediation is related to the parasocial relationship between adolescents and influencers. Active mediation is negatively associated with adolescents’ materialism, whereas restrictive mediation is positively related to adolescents’ purchase intentions towards influencer-promoted products. This study proposed and tested a comprehensive conceptual model that accounts for the role of influencers in adolescent followers’ materialism and purchase intentions. This study yields three major theoretical contributions. First, it adopts and applies the concept of parasocial relationship from the literature of media psychology to explicate influencers’ appeal among adolescents, which lays a theoretical foundation for future research on the impact of influencers. Second, it advances the current literature on social media influencers by specifying key contributing factors for the development of adolescents’ parasocial relationship with influencers. Lastly, it explores the roles of the two facets of parental mediation – active and restrictive mediation – in the appeal of influencers among adolescents, which offers directions for future research of parental mediation in the influencer context.